Modeling and Optimization of Rectangular Latent Heat Storage Elements in an Air-Guided Heat Storage System - Grabo, Matti; Staggenborg, Christoph; Philippi, Kai A.; Kenig, Eugeny (Frontiers in Energy Research, 2020)
The thermal performance of macro-encapsulated latent heat storage elements in form of thin, rectangular plates within an air-driven heat storage system is investigated. The plates are made of high-density polyethylene and filled with phase change material. Several plates are stacked together and inserted into a box which can be installed in a heating / air conditioning system. First, an experimental test rig was designed. Measured temperature and pressure drop data retrieved from the rig was then used to validate a simplified computational fluid dynamics model describing a section of the test set-up including a stack of ten plates. Afterwards, the model was further reduced in complexity in order to perform a parametric study by varying geometric parameters of the storage plates. In total, 217 different geometries were simulated and their thermo-hydraulic efficiency was evaluated. As a result, geometries were proposed, which can potentially increase the thermo-hydraulic efficiency of the storage plates by over 50%.